The Influence of Financial Compensation, Social Security and Non-Financial Compensation on Job Satisfaction of Civil Servants at the Labuhanbatu Regency Transportation Service - Khairul Azmi; Meisa Fitri Nasution; Abd Halim (PT Mattawang Mediatama Solution, 2023)
This study aims to determine the effect of financial compensation, social security and non-financial compensation on job satisfaction of civil servants at the Labuhanbatu Regency Transportation Service, both partially and simultaneously. Determination of the sample technique uses Arikunto's opinion with a total of 40 people and the analytical method used is a descriptive analysis method, multiple linear regression analysis, and hypothesis testing. The results of partial hypothesis testing (t test) show that financial compensation (X1), social security (X2) and non-financial compensation (X3) have a positive and significant effect on job satisfaction of civil servants in the Labuhanbatu Regency Transportation Service, with a variable value of Compensation financial tcount is 3.018 while t table is 1.689 (tcount is bigger than ttable). the social security variable tcount is 3.138 while t table is 1.689 (tcount is bigger than ttable). Meanwhile for the Non-financial Compensation variable the value of tcount is 2,608 while ttable is 1,689 (t count is greater than ttable). The results of simultaneous hypothesis testing (F test) show that Financial Compensation (X1), Social Security (X2), Non-Financial Compensation (X3) have a positive and significant effect on Job Satisfaction of Civil Servants in the Labuhanbatu Regency Transportation Service, with an fcount of 10.371 while ftable 2.64 (fcount is bigger than ftable). The test results for the coefficient of determination (R2) show that the Adjusted R square value is 0.419 or 41.9% indicating that financial compensation, social security and non-financial compensation simultaneously contribute to employee job satisfaction by 41.9%.